2004
DOI: 10.1038/nn1359
|View full text |Cite
|
Sign up to set email alerts
|

Protection of p27Kip1 mRNA by quaking RNA binding proteins promotes oligodendrocyte differentiation

Abstract: The quaking (Qk) locus expresses a family of RNA binding proteins, and the expression of several alternatively spliced isoforms coincides with the development of oligodendrocytes and the onset of myelination. Quaking viable (Qk(v)) mice harboring an autosomal recessive mutation in this locus have uncompacted myelin in the central nervous system owing to the inability of oligodendrocytes to properly mature. Here we show that the expression of two QKI isoforms, absent from oligodendrocytes of Qk(v) mice, induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
195
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(206 citation statements)
references
References 48 publications
11
195
0
Order By: Relevance
“…QKI is a mammalian RNAbinding protein that regulates translational control (50), alternative splicing (51), RNA export (52), and RNA stability (53,54). The identification of the same binding site for BBP and QKI is not surprising since there is 70% sequence identity (14 of 20 amino acids) and 85% sequence similarity (17 of 20 amino acids) in the residues contacting the core UACUAAC sequence.…”
Section: Specificity Of Bbp Compared With Other Kh Domain Proteins-mentioning
confidence: 99%
“…QKI is a mammalian RNAbinding protein that regulates translational control (50), alternative splicing (51), RNA export (52), and RNA stability (53,54). The identification of the same binding site for BBP and QKI is not surprising since there is 70% sequence identity (14 of 20 amino acids) and 85% sequence similarity (17 of 20 amino acids) in the residues contacting the core UACUAAC sequence.…”
Section: Specificity Of Bbp Compared With Other Kh Domain Proteins-mentioning
confidence: 99%
“…Because other types of QRE elements have also been described (9-12), we therefore attempted to find other QREs for the remaining three genes (CDKN1B, MAG, and TF). An experimentally verified QRE that contains the bipartite consensus sequence has been identified in the coding sequence of Cdkn1b in mouse (10). In human CDKN1B, the sequence of the mouse QRE is fairly well conserved ( Fig.…”
mentioning
confidence: 99%
“…The Qki gene contains an RNA-binding domain (KH domain) that binds directly to cellular RNA (8). Several different sequence motifs have been identified as targets for the Qki protein (9)(10)(11)(12). One of these Qki response elements (QREs) consists of a bipartite consensus sequence that has been shown to bind the Qki protein in vivo in at least 23 different mouse mRNA species (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of cell-cycle inhibitors in oligodendrocyte differentiation was further suggested by reports of alternative biological functions for these molecules. P27Kip, for instance, was identified as part of a transcriptional complex activating the MBP promoter (Miskimins et al 2002), as well as part of a complex with specific RNA-binding proteins like Qki (Larocque et al 2005). Despite these exciting findings, overexpression of cell-cycle inhibitors per se was not sufficient to induce differentiation (Tikoo et al 1998;Tang et al 1999) and suggested that additional events must be responsible for the differentiation of progenitors into mature oligodendrocytes.…”
Section: Model 3 Differentiation Consequent To Hdac-mediated Repressimentioning
confidence: 99%